2022
DOI: 10.34172/thj.2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tobacco Use and the Factors Affecting It: A Cross-sectional Analysis of Baseline Data From the Bandare Kong Cohort Study in Southern Iran

Abstract: Background: Tobacco use (TU) has been increasing in Iran and turned into a major national healthcare concern. Therefore, the present research aimed to explore the prevalence of TU and its predictors in Bandar Kong in the south of Iran. Materials and Methods: The baseline data from the Bandare Kong Cohort Study were used in a prospective study of 4,035 subjects (40-70 years old) in Hormozgan province from 2016 to 2018. Adjusted and crude odds ratios (OR) were used at 95% confidence interval (CI) to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Hookah has been used in the Middle East for centuries 2 . Hookah use has been raised as an important problem in Arabian countries, Turkey and Iran 3–9 . According to a review study in 2022, the prevalence of hookah consumption in the world was 9.6%, with the Eastern Mediterranean region (10.7%) having the highest prevalence after Europe (10.9%) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hookah has been used in the Middle East for centuries 2 . Hookah use has been raised as an important problem in Arabian countries, Turkey and Iran 3–9 . According to a review study in 2022, the prevalence of hookah consumption in the world was 9.6%, with the Eastern Mediterranean region (10.7%) having the highest prevalence after Europe (10.9%) 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 Hookah use has been raised as an important problem in Arabian countries, Turkey and Iran. 3 , 4 , 5 , 6 , 7 , 8 , 9 According to a review study in 2022, the prevalence of hookah consumption in the world was 9.6%, with the Eastern Mediterranean region (10.7%) having the highest prevalence after Europe (10.9%). 10 The prevalence of hookah smoking has increased significantly in Iran: form 0.2% in 2016 to 4.5% in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that waterpipe consumption generates 100 times more fume than a cigarette, and this fume contains large amounts of carcinogenic materials such as hydrocarbons and heavy metals. Waterpipe consumption is associated with important conditions, including cardiovascular diseases, infectious diseases, oral cancer, lung cancer, diminished respiratory function, systolic and diastolic hypertension, palpitations, and diminished fertility (6,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%